79.1k views
5 votes
Two equivalent expressions are shown in the equation

where a and b are both integers.
a(7x + 3) = b + 14x

User Xll
by
5.3k points

1 Answer

1 vote

Answer:

3a-b=14x-7ax

Explanation:

Two equivalent expressions are shown in the equation :

a(7x + 3) = b + 14x

Let it assumed to form an equation in terms of a and b.

Opening brackets of both sides,

7ax+3a=b+14x

Taking constant terms to LHS and variables to RHS

3a-b=14x-7ax

Hence, the equation is "3a-b=14x-7ax".

User Wrren
by
5.7k points